THE INFLUENCE OF SOCIAL MEDIA TECHNOLOGY ON STUDENTS' READING INTEREST AT SMA NEGERI 1 MOGA PEMALANG REGENCY - Yuli Arisandi; Suriswo; Munadi (SOSIOEDUKASI, 2026)
This research is motivated by the high intensity of social media use that has the potential to distract students from in-depth reading activities, even though students' literacy competency achievements are relatively adequate. The purpose of the study was to determine the effect of social media technology on students' reading interest at SMA Negeri 1 Moga. The research method used a quantitative approach with a correlational design. The study sample consisted of 292 students determined using proportional random sampling techniques. Data analysis was conducted using prerequisite tests and simple linear regression. The results showed that students' reading interest was generally in the low to moderate category, but the aspect of finding reading content on social media was classified as high. There was a positive and significant influence of social media technology on reading interest with a contribution of 30.8%. It was concluded that social media plays a significant role in influencing students' reading interest. It is recommended that schools implement pedagogical strategies to direct the use of social media as a means of supporting constructive literacy.